Entrepreneurial risk smart / Oswald Timothy Edward … [et al.] - Timothy Edward, Oswald; Mohd Arifin, Azitadoly; Harun, Nurul Aida; Mohd Shahren, Norfaezah; Mohamad Basir, Faziatul Amillia (Division of Research and Industry Linkages, 2017)
In life we are always exposed to risks of one sort or another, in whatever we may be doing, wherever we are, at work or at home. Unfortunately, we must live with some of these risks, since there is little we can do about them. However, there are ways of managing the risks, and there are ways of spreading risks - risk sharing. Insurance comes into picture. Unfortunately, many people find the word 'insurance' a taboo and always try not to engage in it as a result of lack of exposure. This leads to increased risk exposures which could possibly result to potential loss to potential entrepreneurs. Thus, we designed ’Entrepreneurial RiskSmart’ which is an innovative package of risk management and insurance educational tool for potential entrepreneurs. This innovative package is work of art to help potential entrepreneurs profiling their risks and managing them in a smart way. It is a well-balanced treatment on the subject of risk and insurance, This package is designed by experienced lecturers - who have served the insurance industry in one way or another, thus provide vast reference to the local context which is a rarity in Malaysia. In a nutshell, Entrepreneurial RiskSmart’ is an integrated educational tool which can serve multiple users to be smart risk managers. As such, it has high potential to be commercialized to prospective entrepreneurs and business undergraduates.